A review of plastic materials selection software. (4th August 2014) - Mumby, Alan T.; Lewis, Alan; Brown, Robert
The selection of the most appropriate plastic material for a given design application and/or manufacturing process is often problematical. A number of software products are currently available which claim to offer partial or complete solutions to this problem. This paper provides a review of three such products from the perspective of the design engineer. The review arises from a project at the Design Engineering Research Centre of Cardiff Institute of Higher Education to develop a plastic materials selection program. The project has been funded by the Higher Education Funding Council for Wales's Professional, Industrial and Commercial Updating (PICKUP).